Political participation through social media in Malaysia: a review of literature / Wardatul Hayat Adnan and Raz Azira Md Ramly - Hayat Adnan, Wardatul; Md Ramly, Raz Azira (Centre For Media And Information Warfare Studies, 2021)
The advancement of technologies nowadays is becoming important in political participation. As the game changer in political participation nowadays are impacted from new technologies generally and social media specifically. Social media application has significantly played a significant role in government decision. Changing of trend in debating and making decision on any political participation has now aggressively been done through social media. The usage of cyberspace relating to political participation in Malaysia has been increasing since 1990’s. Therefore, the present study will proceed with an overview of social media impact towards political participation in Malaysia. Series of literature review conducted to identify the impacts and trends in Malaysia. In addition, related policy pertaining to social media and politics also will be further elaborate for better understanding on policy matters. The increase of political participation through social media in Malaysia witnessed the trend of more integrated social media tools usage which need to be taken as an important tool in monitoring and winning the society in Malaysia politics game plan. In addition, there are some distinguishable in the development of social media use in politics participations among Malaysian. This evolutionary seems to be useful to understand very different social and political participation using very different levels of technological sophistication that can deliver faster information at almost real time.